Feedforward Control Algorithms for MEMS Galvos and Scanners - Barrett, Lawrence K.; Imboden, Matthias; Javor, Joshua; Campbell, David K.; Bishop, David J. (Journal of microelectromechanical systems, 2021)
Optical systems typically use galvanometers (galvos) and scanners. Galvos move, quasi-statically, from one static position to another. Scanners move in an oscillatory fashion, typically at the device resonant frequency. MEMS devices, which have many advantages and are often used in optical systems, are typically high Q devices. Moving from one position to another for a galvo or one amplitude to another for scanners, can take many periods to settle following the ring down. During these transitions, the optical system is inactive. Here, we show how precisely timed pulses can be used (in an open loop manner) to begin or end scanner motion without ring up/ring down time. The size of pulse required is found to depend on the Q of the device, and relationships are derived. The pulse can also be separated into multiple pulse spaced one period apart if pulses of the necessary size are not possible due to constraints of the physical device. For finite Q scanners, the amplitude decreases after the initial pulse due to damping. This can be eliminated by applying an excitation at the frequency of the scanner. The necessary amplitude for this excitation is derived. Finally, by combining this open loop control algorithm with an open loop control algorithm for galvo motion the device can seamlessly move between scanner and galvo functioning. These control algorithms are demonstrated using computer simulations, analytical models and a commercially available MEMS mirror (Mirrorcle Technologies, A8L2.2). [2020-0238]